INCLUSIVE CHALLENGES IN EDUCATION POLICY: NEP 2020 ERA: PROMISES, PRACTICES, AND PITFALLS (Lex localis - Journal of Local Self-Government, 2025)
India’s National Education Policy (NEP) 2020 articulates an ambitious vision of equitable and inclusive education spanning early childhood to higher education. This paper critically interrogates the “promise–practice” gap that has emerged in the initial implementation phase. We synthesize recent policy circulars, administrative data, and contemporary scholarship to assess progress on inclusion for socio-economically disadvantaged groups, children with disabilities, linguistic minorities, and first-generation learners. Our analysis highlights four cross-cutting fault lines: (i) uneven state capacity and financing that constrain foundational infrastructure, teacher professional development, and assistive technologies; (ii) curricular and assessment transitions that outpace classroom preparedness, creating new forms of exclusion through digital and language demands; (iii) regulatory fragmentation and variable institutional autonomy that weaken accountability for inclusive outcomes; and (iv) data deficits that inhibit continuous, equity-sensitive monitoring. At the same time, promising practices—multilingual pedagogy pilots, low-cost assistive solutions, bridge and remedial programs, and community-based participation—indicate feasible pathways to narrow disparities. We argue that translating the NEP’s inclusion rhetoric into classroom reality requires a sequenced implementation strategy: ring-fenced financing for inclusion, statewide teacher upskilling aligned to curricular change, robust accessibility standards, and disaggregated monitoring linked to corrective support rather than punitive compliance. The conclusion proposes a practicable roadmap that centers the learner’s context and prioritizes “no-exclusion by design” in policy roll-out.